A fully textile-based skin pH sensor. Issue 1 (June 2022) - Choi, Min-Young; Lee, Minji; Kim, Ji-Hye; Kim, Sooyoung; Choi, Jonghoon; So, Ju-Hee; Koo, Hyung-Jun
This paper presents a textile-based pH sensor with high flexibility fabricated by printing a polymer composite as a working electrode and Ag/AgCl/solid electrolyte as a reference electrode on a textile substrate. The textile working electrode is composed of polyaniline, carbon nanotubes, and agarose printed on the textile. A thermoplastic polyurethane overlayer hot-pressed on the textile substrates provides a smooth hydrophobic surface, enabling a more stable formation of the composite films with a reliable output signal. The textile reference electrode is fabricated by printing Ag/AgCl paste and solid electrolyte. The fully textile-based pH sensor, by integrating the textile working and reference electrodes, exhibits a good sensitivity of 45.9 mV/pH with high linearity. The textile pH sensor maintains excellent performance and repeatability with 93% retention even in a bent state and after 1000 bending cycles. Finally, it is demonstrated that the textile pH sensor can detect the pH change on a piece of porcine skin. Graphical Abstract